2019
DOI: 10.1503/cjs.006918
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of chronic isolated scapholunate interosseous ligament injuries: a systematic review of 805 wrists

Abstract: Background: Management of chronic isolated scapholunate interosseous ligament (SLIL) injuries has generated a substantial volume of low-quality literature with descriptions of multiple new surgical techniques, and the impact of instability pattern and the optimal surgical technique remain unclear. The primary goal of this review was to compare clinical, radiographic and patient-rated outcomes between current surgical techniques. Methods: We performed a systematic literature search using multiple databases. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 66 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…Comparison of the pre-and postoperative outcomes against uninjured side demonstrated a statistically significant improvement in mean grip strength (67.0% v. 82.6%), Disabilities of the Arm, Shoulder and Hand (DASH) score (42.2 v. 18.5) and Patient-Rated Wrist Evaluation (PRWE) score (79.6 v. 32.1). 15 There was also statistically significant reduction in the Visual Analogue Scale (VAS) score for pain (4.9 v. 3.0) and wrist flexion (52.3 v. 46.3 ) with p < .05 for all. 7 Radiological parameters (reported in 26 studies) showed a reduction of the SLG from 3.1 mm to 2.7 mm (p ¼ .05) whilst the SLA showed a change from 62 to 57.9 (p < .05).…”
Section: Managementmentioning
confidence: 93%
See 4 more Smart Citations
“…Comparison of the pre-and postoperative outcomes against uninjured side demonstrated a statistically significant improvement in mean grip strength (67.0% v. 82.6%), Disabilities of the Arm, Shoulder and Hand (DASH) score (42.2 v. 18.5) and Patient-Rated Wrist Evaluation (PRWE) score (79.6 v. 32.1). 15 There was also statistically significant reduction in the Visual Analogue Scale (VAS) score for pain (4.9 v. 3.0) and wrist flexion (52.3 v. 46.3 ) with p < .05 for all. 7 Radiological parameters (reported in 26 studies) showed a reduction of the SLG from 3.1 mm to 2.7 mm (p ¼ .05) whilst the SLA showed a change from 62 to 57.9 (p < .05).…”
Section: Managementmentioning
confidence: 93%
“…In static instability the SLIL is injured along with the extrinsic ligaments and consequently, the above-mentioned features are seen in a standard radiograph, without the need for loading/stressing the joint. 7,15 In 1996, Geissler et al popularised the arthroscopic evaluation of SLIL using a 4-stage grading system. 16 Grade 1e3 of this intraoperative classification represent pre-dynamic instability whereas grade 4 is equivalent with dynamic instability.…”
Section: Classificationmentioning
confidence: 99%
See 3 more Smart Citations